Simultaneous interrogation of interferometric and bragg grating sensors - Kalli, Kyriacos; Johnson, David A.; Webb, David J. (My University, 1995)
A new method for the simultaneous interrogation of conventional two-beam interferometers and Bragg grating sensors is proposed and demonstrated. An unbalanced Mach-Zehnder interferometer illuminated by a low coherence source is used to act as a wavelength tunable source for the grating and as a path matched filter for a Fizeau cavity. The technique gives high phase resolution. The grating sensor gave a dynamic strain resolution of ≈0.05 με/√Hz at 20 Hz and the interferometric resolution was better than 1 mrad/√Hz at 20 Hz, corresponding to an rms mirror displacement of 0.08 nm.
Keywords: Bragg gratings; Diffraction gratings; Mirrors; Interferometry